Ethnic Minority Conflicts and Governance in Nigeria - Rotimi T. Suberu (IFRA-Nigeria, 1996)
Ethnic Minority Conflicts and Governance in Nigeria explores and analyses the underlying sources and salient features of recent ethnic minority conflicts in Nigeria, the largely controversial policies by which the Nigerian state has sought to contain these conflicts, and the prospects and preconditions for a more stable and equitable system of federal governance in the country. Through an insightful examination of two most recent minority conflicts in the country, the author probes the contem...